2021
DOI: 10.21037/atm-21-1495
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of giant hiatal hernia for elderly patients

Abstract: Background: Giant hiatal hernias are more common in older patients and can significantly reduce their quality of life. However, open surgery for patients of advanced age is thought to be associated with high morbidity and mortality. The aim of this retrospective study was to evaluate the safety of laparoscopic giant hiatal hernia repair for elderly patients as compared to younger patients.Methods: From January 2015 to January 2020, 152 consecutive patients underwent laparoscopic mesh repair of giant hiatal her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It may have a primary or secondary shortened esophagus, but today most surgeons doubt its real existence, therefore treatment of HH associated with a short esophagus is still a matter of controversy. [6][7][8][9] The symptoms are usually chronic, associated with GERD, heartburn, chest pain, lack of gastric emptying, early satiety, and dysphagia as one of the most common complaints, but in the case of gastric volvulus, they may have an acute and life-threatening condition if ischemia or necrosis develop as the fourth case presented here. Therefore, surgical repair is recommended, but recurrence is very high as reported with a wide range between 12 to 65%.…”
Section: Discussionmentioning
confidence: 93%
“…It may have a primary or secondary shortened esophagus, but today most surgeons doubt its real existence, therefore treatment of HH associated with a short esophagus is still a matter of controversy. [6][7][8][9] The symptoms are usually chronic, associated with GERD, heartburn, chest pain, lack of gastric emptying, early satiety, and dysphagia as one of the most common complaints, but in the case of gastric volvulus, they may have an acute and life-threatening condition if ischemia or necrosis develop as the fourth case presented here. Therefore, surgical repair is recommended, but recurrence is very high as reported with a wide range between 12 to 65%.…”
Section: Discussionmentioning
confidence: 93%
“…Surgical technique problems aside, increased abdominal pressure is an important cause of recurrence of esophageal hiatal hernia, speci cally obesity and gibbus [8,9,24]. Furthermore, the tissues of the esophageal hiatus, including the crus of the diaphragm, are often fragile in the elderly, with being old itself considered a risk factor for postoperative recurrence [10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported acute complications of giant hiatal hernia, such as acute gastric volvulus, intrathoracic gastric perforation, and incarcerated obstruction of the herniated viscera. 2 The presentation of symptoms is usually nonspecific and in most cases the diagnosis results from an imaging study finding.…”
Section: Discussionmentioning
confidence: 99%